Blood glucose levels within 7 days after birth in preterm infants according to gestational age - Ju Young Yoon; Hye Rim Chung; Chang Won Choi; Sei Won Yang; Beyong Il Kim; Choong Ho Shin (Korean Society of Pediatric Endocrinology, 2015)
PurposeThis study investigated blood glucose levels in preterm babies according to gestational age (GA).MethodsSubjects were 141 preterm infants with a GA<34 weeks. Data on blood glucose levels, GA, body weight, glucose infusion rate, and other contributing factors in the first 7 days after birth were analyzed. Hypoglycemia was defined as a blood glucose level of <40 mg/dL up to 24 hours after birth and as <50 mg/dL thereafter. Hyperglycemia was defined as a blood glucose level >180 mg/dL.ResultsDuring the 7 days after birth, hypo- and hyperglycemia occurred in 29 (29 of 141, 20.6%) and 42 (42 of 141, 29.8%) neonates, respectively. During the first 2 hours, 18 neonates (12.8%) exhibited hypoglycemia, and only 2 (2 of 141, 1.4%) developed hyperglycemia. From 6 to 24 hours, hypo- and hyperglycemia were observed in 0 and 9 (9 of 141, 6.4%) neonates, respectively. Infants small for their GA (SGA) were at risk for hypoglycemia both within 24 hours (odds ratio [OR], 2.718; P=0.045) and during days 2 to 7 (OR, 4.454; P=0.006), and hyperglycemia during days 2 to 7 (OR, 3.200; P=0.005). Low 1-minite Apgar score was risk factor for both hypo- and hyperglycemia during days 2 to 7 (OR, 0.756; P=0.035 for hypoglycemia and OR, 0.789; P=0.016 for hyperglycemia). Both hypo- and hyperglycemia within 24 hours were less common in those who started feeding (OR, 0.294; P=0.013 for hypoglycemia and OR, 0.162; P=0.011 for hyperglycemia).ConclusionCareful blood glucose level monitoring is required in preterm infants, especially SGA infants or those with low Apgar score. Early feeding could be beneficial for maintaining euglycemia.